Cost-Effectiveness of Behavior Activation Versus Supportive Therapy on Adherence to Eye Exams in Older African Americans With Diabetes. (November 2017) - Winters, David; Casten, Robin; Rovner, Barry; Murchison, Ann; Leiby, Benjamin E.; Haller, Julia A.; Hark, Lisa; Weiss, David M.; Pizzi, Laura T.
Although the importance of ophthalmologic screening in diabetic patients is widely recognized by clinicians, the cost-effectiveness of strategies aimed at improving eye care utilization in this population is not well established. A cost-effectiveness analysis was performed comparing behavior activation (BA) to supportive therapy (ST) in activating patients to receive a dilated fundus exam (DFE) and promoting healthy management of diabetes. Two hundred six subjects were randomized to receive either BA or ST between 2009 and 2013. Cost-effectiveness was calculated as incremental cost-effectiveness ratio (ICER) of BA versus ST. Total costs for BA and ST per participant were $259.02 and $216.12, respectively. At the 6-month follow-up, 87.91% of BA subjects received a DFE compared to 34.48% of ST subjects. The ICER for BA versus ST was $80.29/percent increase in DFE rate. In terms of improving DFE rates, BA was found to be more cost-effective than ST.